2003
DOI: 10.1034/j.1600-0501.2003.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PRP on autogenous sinus grafts

Abstract: Since platelet -rich plasma (PRP) has been introduced to the field of oral surgery, it has become a widely accepted additive for bone regeneration treatment. The aim of this study was to evaluate the regenerative capacity of PRP in a sinus graft study on sheep. Twelve adult sheep underwent a bilateral sinus floor elevation procedure with cancellous bone from the iliac crest. Unilaterally, PRP was administrated to the bone graft. After 4 (six sheep) and 12 weeks (six sheep), bone biopsies were obtained from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
1
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 9 publications
4
92
1
11
Order By: Relevance
“…The NBA observed in Group AB was similar to that of Group AB/PRP-150. In their animal study, Jakse et al 23 observed no influence of PRP on autogenous bone graft healing, and concluded that PRP showed a quite low regenerative capacity. However, in our study, a significant effect of PRP on graft healing was seen in Group AB/ PRP-50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NBA observed in Group AB was similar to that of Group AB/PRP-150. In their animal study, Jakse et al 23 observed no influence of PRP on autogenous bone graft healing, and concluded that PRP showed a quite low regenerative capacity. However, in our study, a significant effect of PRP on graft healing was seen in Group AB/ PRP-50.…”
Section: Discussionmentioning
confidence: 99%
“…Even though clinical 4,20,21 and animal studies 8,22,23 reported the volume of PRP, they did not describe the volume of autogenous bone graft used. Therefore, the ratio of autogenous bone graft/PRP cannot be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep were used by Jakse et al 30 (autogenous bone and PRP) and by Sarkar et al 31 (collagen sponge and PRP) -in both the studies the results with PRP were not advantageous. Fürst et al 32 , Wiltfang et al 18 and Klongnoi et al 33 use minipigs as experimental animal.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand, some authors did not find any advantages in bone healing when using bone grafts or biomaterials in combination with PRP. [26][27][28][29] Differences in the way of isolating PRP, the use of a specific anticoagulant that could affect platelet fragmentation and effectiveness of GF could be the most important variables affecting literature results. 27 Also, the absence of osteoblasts in anorganic bone grafts and the absence of osteoinductive effects of PRP were hypothesized to be responsible for the poor result obtained by some authors.…”
Section: Discussionmentioning
confidence: 99%